2023
DOI: 10.21037/cco-22-110
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy following neoadjuvant chemotherapy: an evidence-based review and recommendations for current practice

Abstract: Sentinel lymph node biopsy (SLNB) at upfront surgery is the gold-standard surgical method for axillary lymph node staging in early stage breast cancer: the technique provides adequate information regarding axillary status, with similar oncological safety and lower morbidity compared to axillary dissection, despite the false negative rates. Neoadjuvant chemotherapy (NACT), traditionally used for locally advanced breast cancer, plays an important role in the treatment of early stage breast cancer, making downsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Evidence-based data suggest that SLNB in the post NACT setting is considered controversial because of the increased false negative rates that have been observed [53], which is why guidelines recommend the use of the standard dual RI + BD technique in these cases [4]. Therefore, it is reasonable to hypothesize that patients in these circumstances may benefit from adding ICG to the standard dual technique.…”
Section: Icg As Slnb Tracer In the Post Nact Settingmentioning
confidence: 99%
“…Evidence-based data suggest that SLNB in the post NACT setting is considered controversial because of the increased false negative rates that have been observed [53], which is why guidelines recommend the use of the standard dual RI + BD technique in these cases [4]. Therefore, it is reasonable to hypothesize that patients in these circumstances may benefit from adding ICG to the standard dual technique.…”
Section: Icg As Slnb Tracer In the Post Nact Settingmentioning
confidence: 99%
“…Commonly used NACT regimens for lung cancer include PP scheme (pemetrexed + platinum), TP scheme (paclitaxel + platinum), and GP scheme (gemcit-Am J Transl Res 2024;16 (5):2024-2033 abine + platinum) [8]. Studies have found that NACT can shrink tumors, thereby reducing the scope and difficulty of surgery, as well as decreasing postoperative complications [9,10]. Although various treatment options for patients with stage IIIa-N2 NSCLC have prolonged the survival time of the patients, the 5-year survival rate is still only about 15% [11].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the SLNB has been performed in patients with no evidence of axillary involvement at staging who were submitted to surgery after NACT with FNRs of about 10% and acceptable SLN identification rates [21,[32][33][34][35]. Conversely, until the last decade, patients with verified axillary involvement at staging were submitted to ALND, even in cases of complete response at this level [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, prospective studies on large samples of patients have begun to change this concept, indicating an overall SLN identification rate (SNIR) ranging from 87.6 to 97.2%, but FNRs higher than the accepted 10% are indicated by previous studies [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%